Randomized Controlled Trial of Exercise to Improve Walking Energetics in Older Adults. Issue 3 (8th September 2018) - Collins, Kristina J; Schrack, Jennifer A; VanSwearingen, Jessie M; Glynn, Nancy W; Pospisil, Michelle C; Gant, Veronica E; Mackey, Dawn C
Abstract: Background and Objectives: Mobility limitation is common and has been linked to high energetic requirements of daily activities, including walking. The study objective was to determine whether two separate forms of exercise could reduce the energy cost of walking and secondary outcomes related to activity and participation domains among older adults with mobility limitation. Research Design and Methods: Community-dwelling older adults with self-reported mobility limitation ( n = 72) were randomized to 12 weeks of twice-weekly, group-based, instructor-led timing and coordination, aerobic walking, or stretching and relaxation (active control) programs. The primary outcome was the energy cost of walking (mL O2 /kg/m), assessed by a 5-minute treadmill walking test (0.8 m/s). Secondary outcomes were fatigability, physical activity, endurance, physical function, and life-space. Baseline-adjusted ANCOVAs were used to determine mean differences between exercise and control groups at 12 and 24 weeks. Results: Exercise session attendance was high: 86% for timing and coordination, 81% for aerobic walking, and 90% for stretching and relaxation. At 12 weeks, timing and coordination reduced the mean energy cost of walking by 15% versus stretching and relaxation ( p = .008). Among those with high baseline cost, timing and coordination reduced mean energy cost by 20% versus stretching and relaxation ( p = .055). Reductions were sustained at 24 weeks. Aerobic walking had no effect on the energy cost of walking at 12 or 24 weeks. At 12 weeks, there was a trend toward faster gait speed (by 0.1 m/s) in timing and coordination versus stretching and relaxation ( p = .074). Fatigability, physical activity, endurance, physical function, and life-space did not change with timing and coordination or aerobic walking versus stretching and relaxation at 12 or 24 weeks. Discussion and Implications: Twelve weeks of timing and coordination, but not aerobic walking, reduced the energy cost of walking among older adults with mobility limitation, particularly among those with high baseline energy cost; reductions in energy cost were sustained following training cessation. Timing and coordination also led to a trend toward faster gait speed.